Activation of NF-κB1 by OX40 Contributes to Antigen-Driven T Cell Expansion and Survival - Jianxun Song; Takanori So; Michael Croft (2008)
The costimulatory molecule OX40 (CD134) is required in many instances for effective T cell-mediated immunity, controlling proliferation, and survival of T cells after encountering specific Ag. We previously found that the functional targets of OX40 are survivin and aurora B that regulate proliferation and Bcl-2 antiapoptotic family members that regulate survival. However, the intracellular pathways from OX40 that mediate these effects are unclear. In this study, we show that OX40 signaling can target the canonical NF-kappaB (NF-kappaB1) pathway in peripheral Ag-responding CD4 T cells. Phosphorylation of IkappaBalpha, nuclear translocation of NF-kappaB1/p50 and RelA, and NF-kappaB1 activity, are impaired in OX40-deficient T cells. Retroviral transduction of active IkappaB kinase that constitutively activates NF-kappaB1 rescues the poor expansion and survival of OX40-deficient T cells, directly correlating with increased expression and activity of survivin, aurora B, and Bcl-2 family members. Moreover, active IkappaB kinase expression alone is sufficient to restore the defective expansion and survival of OX40-deficient T cells in vivo when responding to Ag. Thus, OX40 signals regulate T cell number and viability through the NF-kappaB1 pathway that controls expression and activity of intracellular targets for proliferation and survival.